Satellite‐Derived Global Surface Water Extent and Dynamics Over the Last 25 Years (GIEMS‐2). Issue 3 (5th February 2020) - Prigent, C.; Jimenez, C.; Bousquet, P.
Abstract: A method has been developed to extend the Global Inundation Estimate from Multiple Satellites (GIEMS). The method presented here is based on retrieval principals similar to GIEMS but with an updated estimation of microwave emissivity in order to be less dependent on ancillary data and with some changes to the final surface water estimation to correct a known overestimation over low vegetation areas. The new methodology, GIEMS‐2, provides monthly estimates of surface water extent, including open water, wetlands, or rice paddies, and it has been applied to the Special Sensor Microwave/Imager and the Special Sensor Microwave Imager Sounder intercalibrated observations to produce a global data record of surface water extent from 1992 to 2015, on an equal area grid of 0.25° × 0.25° at the equator (∼25 km). The time series have been thoroughly evaluated: they are seamless and do not show any obvious artifact related to changes in satellite instrumentation over the ∼25 years. Comparisons with precipitation estimates show good agreement, displaying expected patterns related to surface conditions and precipitation regimes. The temporal variability of basin‐averaged estimates has also been compared with altimeter river height, showing a reasonable agreement. Production will be continued up to current time as soon as the observations become available, with efforts to improve the spatial and temporal resolutions of the estimates currently underway. Plain Language Summary: A method has been developed to provide global estimates of the continental surface waters and their dynamics. It comprises all surface waters, including open water, wetlands, or rice paddies. With multiple satellite data, a global data record of surface water extent is produced, on a monthly basis from 1992 to 2015, with a spatial resolution of 25 km. The time series have been thoroughly evaluated: They are seamless and do not show any obvious artifact related to changes in satellite instrumentation over the 25 years. Comparisons with precipitation estimates show good agreement, displaying expected patterns related to surface conditions and precipitation regimes. Temporal variability of basin‐averaged estimates has also been compared with altimeter river height, showing a reasonable agreement. Production will be continued up to current time as soon as carefully intercalibrated satellite observations become available, with efforts to improve the spatial and temporal resolution of the estimates currently underway. Key Points: A method is developed to derive a Global Inundation Estimate from Multiple Satellites (GIEMS‐2 product) It provides monthly estimates of surface water extent since 1992, with a spatial resolution of 0.25° × 0.25° The time series have been thoroughly evaluated and are suitable for climatological studies